Gambaran Perilaku Merokok Pada Remaja SMA Negeri 1 Ende Tahun 2026: Perilaku Merokok Remaja - aprilia chindrania sombo; Yustina Paschalia; Aris Wawomeo (Poltekkes Kemenkes Kupang, 2026)
Background Smoking behavior among adolescents remains an important public health issue because it can lead to nicotine dependence and increase the risk of various diseases. Adolescents are a vulnerable group to environmental influences, especially peers, making them more likely to engage in smoking behavior. Objective To describe smoking behavior among students of SMA Negeri 1 Ende based on smoking frequency, smoking intensity, number of cigarettes consumed, smoking situations, and classification of smoking behavior. Methods This study used a quantitative descriptive design with a cross-sectional approach. The study was conducted at SMA Negeri 1 Ende in May 2026. The population consisted of 151 male students in grades X and XI who had smoking behavior. A sample of 110 respondents was selected using accidental sampling technique. Data were collected using a smoking behavior questionnaire consisting of 23 questions and analyzed using univariate analysis. Results The results showed that most respondents had light-category smoking frequency (83 respondents; 75.5%), light-category smoking intensity (65 respondents; 59.1%), light-category number of cigarettes consumed (82 respondents; 74.5%), and light-category smoking situation (63 respondents; 57.3%). Overall, the majority of respondents were classified as light smokers (65 respondents; 59.1%). Conclusion Smoking behavior among students of SMA Negeri 1 Ende is predominantly classified as light smoking. Health promotion and smoking prevention efforts need to be continuously strengthened to reduce smoking behavior among adolescents